Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis. Issue 1 (15th April 2022) - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al.
Abstract : Objective: Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available. Design: The patient received a single infusion of 1×10 6 autologous, ex vivo expanded, polyclonal Tregs per kilogram of body weight, and the clinical, biochemical, endoscopic and histological responses were assessed 4 and 12 weeks after adoptive Treg transfer. Results: The patient showed clinical, biochemical, endoscopic and histological signs of response until week 12 after adoptive Treg transfer, which was associated with an enrichment of intestinal CD3 + /FoxP3 + and CD3 + /IL-10 + T cells and increased mucosal transforming growth factor beta and amphiregulin levels. Moreover, there was marked improvement of PSC with reduction of liver enzymes. This pronounced effect lasted for 4 weeks before values started to increase again. Conclusion: These findings suggest that adoptive Treg therapy might be effective in refractory UC and might open new avenues for clinical trials in PSC. Trial registration number: NCT04691232 .